(untitled) (Dimensión Empresarial, 2020)
The health tourism sector in Colombia has been increasing its recognition at the international level, mainly for determining factors of quality and costs, which is how it becomes a significant factor for the economy measured through GDP. In this perspective, the Kano model can allow the identification of the needs and requirements of the users, in order to improve the standards and coverage currently offered by said sector.